The Status of Children Due to Underhanded Marriages after Marriage is Recorded without Marriage Isbat - Iskhaq Iskhaq; Sri Kusriyah (UNISSULA Semarang, 2021)
This study aims to determine the status of children due to underhanded marriages whose parents have remarried (new) and are registered with the Marriage Registrar, without marriage isbat for their previous marriages. This study uses a normative juridical research method, which focuses on examining the laws and regulations and the determination of the Religious Courts regarding the status of children born as a result of underhanded marriages. Based on the results of the study, it can be concluded that the Religious Courts in determining the application are guided by the rule that the legal status of a child born as a result of an underhand marriage depends on the validity of the marriage (marriage contract) of both parents which at that time was carried out under the hands, namely the marriage must meet the pillars and conditions of marriage and there are no obstacles to marriage according to Islamic law in accordance with statutory regulations. If these things are not fulfilled, then the child's status is only related to his mother and his mother's family. The re-marriage (new) that is registered is not retroactive so that it does not necessarily have legal consequences on the legitimacy of the child.